Prevalensi bayi lahir cacat (Malformasi Kongenital) di Rumah Sakit Pendidikan Fakultas Kedokteran Universitas YARSI - Mustofa, Samsul; Susmiarsih Panjiasih, Tri; Wikaningrum, Riyani (Jurnal Kedokteran YARSI, 2009)
Congenital Malformations was instrumental in perinatal morbidity and infant mortality. Patients with severe disorders are classified to be affected physically, mentally, and socially and require special attention. Prevalence data from various types of congenital malformations may be useful to plan primary prevention measures for such disorders. The purpose of this study was to examine the prevalence of congenital malformations at the teaching hospitals, Faculty of Medicine, YARSI University. In this study, data were obtained from medical records in four teaching hospitals i.e. Abdul Muluk Hospital in Bandar Lampung, Lampung, Serang General Hospital in Serang, Banten, Garut General Hospital in Garut, and Gunung Jati General Hospital in Cirebon, West Java, within a period of three years i.e. 2005 to 2007. Based on ICD-10 codes, eight groups involving 18 types of birth defects were recorded. Among 25,276 babies born in four previously mentioned hospitals, 283 babies were born with congenital malformation. The prevalence of congenital malformations in Abdul Muluk Hospital was 11.31% with the frequency of 5.961/1,000 live birth, Serang Hospital was 13.78% with the frequency of 7.163/1,000 live birth, Garut Hospital was 33.92% with the frequency of 9.777/1,000 live birth and Gunung Jati Hospital was 40.99% with the frequency of 24.98/1000 live birth. Various disorders were noted, being the most common was disorder in the digestive system (25.80%), followed by the musculoskeletal system (20.49%), and the nervous system (16.61%). In conclusion, the total prevalence of congenital malformations in the teaching hospital, Faculty of Medicine, YARSI University was 1.12% with the frequency of 11.2/1000 live births. Congenital malformations were particularly prominent in Gunung Jati General Hospitals Cirebon, West Java.